Pengaruh Intercritical Quenching dan Normalizing terhadap Laju korosi dan Struktur Mikro Mild Steel - Nurhabibah Paramitha Eka Utami; Diah Kusuma Pratiwi; Hendri Chandra; Randi Gaga Pisasefsio Pratama (Universitas Sriwijaya, 2023)
Corroded materials get promote to the decrease in physical and mechanical properties which will affect to the decrease in the quality of the material and will have a huge impact on the industrial world. The purpose of this research is to observe the effect of the intercritical heating temperature of 750 °C with the quenching and normalizing cooling method due to the corrosion rate and its effect on the phenomenon of hardness change values in mild steel. The tests that was conducted are corrosion testing and hardness testing on ASTM A36. The results showed that there was a significant decrease in the corrosion rate and hardness values in the normalizing test sample, while in the quenching test sample there was an increase in the hardness value which that led to the presence of a ferrite – martensite dual phase on the surface of the quenching specimen which reduced ductility and increased the hardness value of mild steel. Keywords: ASTM A36, Corrosion, Micro structure, Quenching, Normalizing